2021
DOI: 10.1017/jns.2021.78
|View full text |Cite
|
Sign up to set email alerts
|

Diet-dependent entropic assessment of athletes’ lifespan

Abstract: Life expectancies of the athletes depend on the sports they are doing. The entropic age concept, which was found successful in the previous nutrition studies, will be employed to assess the relation between the athletes’ longevity and nutrition. Depending on their caloric needs, diets are designed for each group of athletes based on the most recent guidelines while they are pursuing their careers and for the post-retirement period, and then the metabolic entropy generation was worked out for each group. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In the present study, the second law analyses are performed. This study was formulated with the same principles as those of Öngel et al [29], Yildiz et al [65,66] and Semerciöz et al [67] and offers thermodynamic assessment to the issue of whether pregnancy affects longevity of the women or not. Todhunter et al [68] achieved documenting the consequences of entropy accumulation in the tissues visually.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the second law analyses are performed. This study was formulated with the same principles as those of Öngel et al [29], Yildiz et al [65,66] and Semerciöz et al [67] and offers thermodynamic assessment to the issue of whether pregnancy affects longevity of the women or not. Todhunter et al [68] achieved documenting the consequences of entropy accumulation in the tissues visually.…”
Section: Resultsmentioning
confidence: 99%
“…In this field, the diet dependence of the entropy generation and accumulation rates of a living system is emerging as a promising tool for developing personalized nutrition strategies [ 29 , 35 , 38 ]. The grey mouse lemur model results showed that long-term n-3 PUFA supplementation increased the entropy generation rate and decreased Gibbs free energy in the whole brain and specific brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of metabolite pathways and thermodynamic systems is mutually beneficial. By frequently measuring the thermodynamics of biological systems at both the molecular and systemic levels, we can gain insights into the efficiency of biological organisms under different conditions [ 12 , [14] , [15] , [16] , [20] , [21] , [22] , [23] , [26] , [27] , [28] ].…”
Section: Discussionmentioning
confidence: 99%
“…Exergy analysis helps to separate inefficiencies of the system that occur due to effluent losses and those due to irreversibilities. Fundamental principles of thermodynamics including exergy analysis have been extensively used to study metabolism [ 12 , [19] , [20] , [21] , [22] , [23] ] and systems interaction with surroundings within the context of thermal body comfort [ 24 , 25 ], aging or the effect of the physical activity level on lifespan entropy generation [ [26] , [27] , [28] ]. In mammalian cells, energy balance regulation of metabolism has long been a subject of investigation, in particular, regulation of mitochondrial energy synthesis has been a prior interest [ 16 , 29 ].…”
Section: Introductionmentioning
confidence: 99%